Feelings of Incompetence in Novice Therapists: Consequences, Coping, and Correctives - Thériault, Anne; Gazzola, Nicola; Richardson, Brian (Canadian Journal of Counselling and Psychotherapy, 2009)
Feelings of self-doubt and insecurity about one’s effectiveness are frequently reported by mental health professionals, regardless of their experience level. In novice therapists, feelings of incompetence (FOI) are a central feature in the development of their professional identity. A first-person perspective of FOI will provide insight into its impact and its potential resolution. Ten novice therapists discussed their FOI during a 45–90 minute semi-structured interview. The authors analyzed the transcripts using procedures inspired by grounded theory methodology and distilled a conceptual scheme outlining consequences, coping mechanisms, and self-care training needs. Implications for counsellor education and supervision are discussed briefly.